2009
DOI: 10.1007/s11270-009-9992-0
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Cd, Pb, Ra and U from Phosphogypsum Amended Soils to Tomato Plants

Abstract: About 170 million tons of phosphogypsum (PG) are annually generated worldwide as a byproduct of phosphoric acid factories. Agricultural uses of PG could become the main sink for this waste, which usually contains significant radionuclide (from the 238 U-series) and toxic metals concentrations. To study PG effects on pollutant uptake by crops, a completely randomised greenhouse experiment was carried out growing Lycopersicum esculentum Mill L. on a reclaimed marsh soil amended with three PG rates (treatments), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…Pb in chards constitutes the exception with a slightly higher concentration than the maximum accepted one. For the majority of elements, we observed that leaf vegetables accumulate more metals than fruit vegetables, a fact that has already been described in the literature (Di Salvatore et al, 2009;Enamorado et al, 2009;Golia et al, 2008). The only exception is copper with similar concentrations in pepper, tomato, artichoke and chard.…”
Section: Analysis Of Other Vegetables Sampled In the Orchard Located supporting
confidence: 82%
See 1 more Smart Citation
“…Pb in chards constitutes the exception with a slightly higher concentration than the maximum accepted one. For the majority of elements, we observed that leaf vegetables accumulate more metals than fruit vegetables, a fact that has already been described in the literature (Di Salvatore et al, 2009;Enamorado et al, 2009;Golia et al, 2008). The only exception is copper with similar concentrations in pepper, tomato, artichoke and chard.…”
Section: Analysis Of Other Vegetables Sampled In the Orchard Located supporting
confidence: 82%
“…Moreover, the distribution of metals and metalloids among organs of tomato plants (roots, leaves, fruits, stem) is not fully resolved. There is a consensus to accept that distribution rates seem to be metal-specific (Di Salvatore, Carratù, & Carafa, 2009;Perez-Espinosa et al, 2005), and that most of the metals tend to accumulate in roots and leaves rather than in fruits (Enamorado et al, 2009;Li et al, 2010). Initially, a correlation between the concentration of metals in soil and that in the edible part is not expected to be general since it depends on soil characteristics and plant physiology.…”
Section: Introductionmentioning
confidence: 99%
“…The highest rate mimics the cumulative effect of a typical application during 20-30 years in the area. Phosphogypsum (from a non-active stack in Huelva, Spain, disposal site) properties are described elsewhere (Enamorado et al, 2009;Hurtado et al, 2011a). Total nutrient contents of PG were (all in g kg -1 ): P (3.5), S (150), Ca (229), B (3.1), Fe (0.4), Cu (0.0052), Mn (0.0003), Zn (0.011), Ni (0.012) and Mo (0.0009); beside this, its content in Na was 0.3 g kg -1 ; the content of N, K and Mg was not detectable.…”
Section: Plant Materials and Cultivation Conditionsmentioning
confidence: 99%
“…However, the use of PG in reclaimed marsh soils from SW Spain has been shown to increase P availability index in soils (Domínguez et al, 2001). Beside this, fluoride, transition metals, boron and trace elements are present in PG (Enamorado et al, 2009). These elements can affect plant nutrition, not only by the supply, but also by the dissolution of some silicates by fluoride which can result in the potential release of toxic elements such as Al (Mariscal-Sancho et al, 2009).…”
mentioning
confidence: 99%
“…Also, an increasing price of P fertilizer can be partially offset by decreasing fertilizer manufacturing costs such as by using unprocessed phosphate rock (PR) ( Vassilev et al, 2009; Vassileva et al, 2010). Direct use of PR can also alleviate environmental concerns arising from P fertilizer production ( Enamorado et al, 2009). However, PR is typically composed of highly insoluble Ca‐phosphates (usually of the apatite type) that are especially inefficient as a P source for calcareous soils.…”
Section: Introductionmentioning
confidence: 99%